The associations of vascular endothelial growth factor gene polymorphisms with susceptibility to osteosarcoma: evidence from a meta‐analysis. (3rd May 2016) - Zhao, J.; Chen, Z.Q.; Li, G.W.; Yang, M.; Shao, J.; Li, M.
Abstract : Several studies have investigated the associations of the vascular endothelial growth factor (VEGF) gene polymorphisms with the susceptibility to osteosarcoma, while their conclusions are conflicting. This meta‐analysis was performed to provide a comprehensive assessment on those associations. Electronic bibliographic databases were searched for potential studies focused on the relationship between VEGF polymorphisms and the susceptibility to osteosarcoma on 10 December 2015. Pooled odds ratios with 95% confidence intervals were conducted to assess the associations. After strict screening process, six articles consisted of 1220 osteosarcoma patients and 1576 controls were selected. The pooled results suggested that VEGF‐2578C/A polymorphism was significantly associated with osteosarcoma risk in all genetic models as well as VEGF‐634G/C polymorphism. When it came to VEGF+936C/T polymorphism, we detected significant associations under allele contrast, heterozygote, dominant and recessive models. As to VEFG‐460T/C polymorphism, significant associations were demonstrated in allele contrast and heterozygote models. With regard to VEGF‐1156G/A polymorphism, significant association was observed only in alleles contrast model. However, there was no significant association between VEGF‐1612G/A polymorphism and risk of osteosarcoma. This meta‐analysis suggests that these polymorphisms comprised of VEGF‐2578C/A, VEGF‐1156G/A, VEGF+936C/T, VEGF‐634G/C and VEGF‐460T/C are associated with osteosarcoma risk in Chinese Han population.